DEVELOPMENT OF CREATIVE ECONOMY PRODUCTS BAKATAK SYRUP IN BATU JONGJONG TOURISM VILLAGE BAHOROK SUB-DISTRICT, LANGKAT REGENCY - Rosari, Dina; Riady, Iwan; Julianto (PT. Hafasy Dwi Nawasena, 2024)
This study aims to explore and analyze the process of developing creative economy products, especially Bakatak Sirup, in Jongjong Stone Tourism Village. The research method used is qualitative with a case study approach. This research involves various parties involved in product development, including Bakatak fruit farmers, local businesses, and other stakeholders. This research focuses on the stages of product development, innovation in formulation and packaging, and the economic and social impact of the product on local communities. In-depth interview methods are used to gain views. in-depth from business actors, while direct observations were made to contextually understand the production process of Bakatak Syrup. The results of this study are expected to provide a deep understanding of how the development of creative economy products can have a positive impact on the local economy and community involvement in the process. Qualitative analysis will be used to identify success factors, challenges faced, and implications of development of creative economy products in Jongjong Stone Tourism Village. This research is expected to contribute to the theoretical and practical understanding of the development of creative economy products at the local level, especially in the context of tourism villages. The findings of this study can be the basis for product developers, local governments, and related institutions to design policies that support the development of the creative economy in the area.